Study the effect of gold nanoparticles on cancer and normal cells (in vitro study) - Hussein, Sumaiah I. (Iraqi Journal of Cancer and Medical Genetics, 2016)
This study was done to evaluation the empact of gold nanoparticles on two cancer cell lines in vitro, HeLa (human cervicle cancer cell line) and AMN3 (mammary adenocarcinoma), in addition to isolated lymphocytes from peripheral blood of healthy human as normal cells, at different concentrations and incubation period. Results shows that cancer cells more effected than normal cells, as well as AMN3 more effected than HeLa cell line, so the effect is related to cells type, concentration, incubation period and size of particles . The present study suggests that gold nanoparticles is a good candidate for medical application as anticancer and needs further studies.